Effects of infusions of catecholamines, angiotensin, vasopressin and histamine on hepatic blood volume in the anaesthetized cat - Greenway, C. V. (1972)
1. Hepatic volume was recorded by a plethysmographic technique in cats anaesthetized with pentobarbitone; the hepatic artery and portal vein remained intact. Dose-response curves were obtained for intravenous infusions of adrenaline, noradrenaline, angiotensin, vasopressin and histamine. 2. Adrenaline and noradrenaline decreased hepatic blood volume and did not differ significantly in potency. Up to 40% of the hepatic blood volume was expelled by doses within the range secreted by the adrenal medullae. 3. Isoprenaline, infused into the hepatic artery, had no significant effect on hepatic blood volume in doses which caused maximal vasodilatation of the hepatic arterial bed. Relaxation of hepatic capacitance vessels mediated by β-adrenoceptors did not occur. 4. Angiotensin infusions in doses previously shown to cause intestinal and splenic vasoconstriction, decreased hepatic blood volume and on a molar or microgramme basis, angiotensin was the most potent of the agents tested. Doses within the probable physiological range of endogenous production decreased hepatic blood volume by up to 20%. The responses were not significantly different when the hepatic nerves were intact or sectioned. 5. Vasopressin infusions produced only small decreases in hepatic blood volume. Doses within the range secreted by the posterior pituitary which constrict the intestinal and splenic resistance vessels, did not decrease hepatic blood volume by more than 10%. 6. Histamine produced no change in hepatic blood volume in doses which readily produce outflow block in dogs. Either the specific hepatic venous smooth muscle involved in outflow block is absent in the cat or it has no histamine receptors. 7. After the rapid change in hepatic blood volume at the onset of the infusion, hepatic volume remained steady for the duration of each infusion. There was no evidence that these agents caused net transsinusoidal fluid movements.